2017
DOI: 10.3389/fimmu.2017.01077
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of Dual Toll-Like Receptor Agonists and Antigen in Poly(Lactic-Co-Glycolic) Acid/Polyethylenimine Cationic Hybrid Nanoparticles Promote Efficient In Vivo Immune Responses

Abstract: Strategies to design delivery vehicles are critical in modern vaccine-adjuvant development. Nanoparticles (NPs) encapsulating antigen(s) and adjuvant(s) are promising vehicles to deliver antigen(s) and adjuvant(s) to antigen-presenting cells (APCs), allowing optimal immune responses against a specific pathogen. In this study, we developed a novel adjuvant delivery approach for induction of efficient in vivo immune responses. Polyethylenimine (PEI) was physically conjugated to poly(lactic-co-glycolic) acid (PLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…Considering that most pathogens need to stimulate multiple TLRs to upregulate pro‐inflammatory cytokines and chemokines, nanovectors are engineered to combine a few TLR agonists. For example, poly( d , l ‐lactic‐ co ‐glycolic acid) (PLGA)/polyethylenimine (PEI) polymeric nanoparticles codeliver R848 (TLR7/8 agonist), MPLA (TLR4 agonist), and CpG (TLR9 agonist) with OVA, exerting superior effects on promoting robust immune responses in comparison to a single bioadjuvant, which is consistent with other studies …”
Section: Nanomaterials For Traditional and Novel Vaccine Deliverysupporting
confidence: 88%
“…Considering that most pathogens need to stimulate multiple TLRs to upregulate pro‐inflammatory cytokines and chemokines, nanovectors are engineered to combine a few TLR agonists. For example, poly( d , l ‐lactic‐ co ‐glycolic acid) (PLGA)/polyethylenimine (PEI) polymeric nanoparticles codeliver R848 (TLR7/8 agonist), MPLA (TLR4 agonist), and CpG (TLR9 agonist) with OVA, exerting superior effects on promoting robust immune responses in comparison to a single bioadjuvant, which is consistent with other studies …”
Section: Nanomaterials For Traditional and Novel Vaccine Deliverysupporting
confidence: 88%
“…Collaboration of multiple PRRs and their adaptors is required for an optimal host response to many pathogens (Delaloye et al, 2009;Ferwerda et al, 2007;Slater et al, 2010). In the context of vaccine-adjuvant development, it has also been shown that co-delivery of TLR agonists as adjuvants elicits an improved immune memory response (Ebrahimian et al, 2017;Pulendran and Ahmed, 2011). Thus, a cogent and effective immune response must involve concomitant engagement of multiple PRR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulator of interferon genes (STING), and nucleotide‐binding oligomerization domain (NOD)‐like receptors are additional PRRs that are present in the cell's cytoplasm and trigger the expression of the three activation signals . Triggering combinations of TLR pathways in APCs (or other synergistic immune pathways) is one developing area to improve understanding of the generation and regulation of a range of immune processes, both innate and adaptive . Another key function of APCs is the connection these cells have to adaptive immunity, which is the focus of the next section.…”
Section: Immune Responses Rely On Coordinated Cell and Tissue Interacmentioning
confidence: 99%
“…Along these lines, helper T cells adopt phenotypes optimized to combat specific classes of pathogens: T H 1 cells help clear intracellular pathogens like viruses and bacterium, while T H 2 cells help clear parasites and pathogens outside the cell. Ebrahimian et al developed a novel signal delivery method using a cationic polymer polyethylenimine (PEI) conjugated to poly(lactic‐ co ‐glycolide) (PLGA) NPs coencapsulating either a TLR7/8 agonist—resiquimod—or a TLR4 agonist—monophophoryl lipid A (MPLA) . These components were coassembled with a TLR9 agonist, CpG, to form NP formulations containing defined combinations of two TLR agonists.…”
Section: Biomaterials Enable Analysis Of Immune Signaling Through Conmentioning
confidence: 99%
See 1 more Smart Citation